Vocabulary Mastery Challenges Among Indonesian Public Junior High School Students - Sinaga, Jonathan Halomoan; Napitupulu, Selviana (CV Putra Publisher, 2026)
Vocabulary mastering is essential in English as a Foreign Language (EFL) learning; however, many Indonesian public junior high school pupils continue to have major lexical weaknesses. The purpose of this study is to look into the lack of vocabulary mastery among seventh- and eighth-grade students at a public junior high school in Indonesia, as well as to discover the underlying causes of this problem. Data for 96 students were acquired using a qualitative descriptive technique, including classroom observations, student interviews, and teacher reports. According to the findings, students displayed inadequate vocabulary recognition, poor retention, and a low ability to utilise words effectively in context. Seventh-grade students had difficulty with basic word memory and expressed significant levels of fear and unwillingness to speak, whereas eighth-grade students struggled with pronunciation, grammatical word forms, and inconsistent vocabulary use. Traditional teaching approaches that emphasise rote memorisation without adequate contextual exposure were found as a primary contributor to children' restricted vocabulary development. The findings also show that a lack of relevant language input and limited possibilities for active vocabulary use had a negative impact on students' confidence and communicative skills. This study finds that enhancing vocabulary mastery necessitates instructional strategies that emphasise contextualised learning, regular exposure, and active participation with high-frequency terms. The findings have pedagogical implications for English teachers and policymakers in Indonesian junior high schools, helping to improve vocabulary training and promote long-term language development.